Construcción del sentido de comunidad en niños, niñas y jóvenes del barrio "San José los Pinos Segunda Etapa" dentro del proceso de legalización de tierras. - Bohórquez Vargas, José Nicanor (2015)
The proyect “Construction of Sense of Community in children and young from the San Jose Los Pinos neighborhood second stage, in the process of legalization of the lands" comes from an agreement of cooperation between psychosocial research center of the “Universidad Politécnica Salesiana” and the "Comité de Desarrollo Comunitario Los Pinos". This project is part of the whole dynamic that " Comité de Desarrollo Comunitario Los Pinos"” carry out about the "Barrio del Buen Vivir" construction, the project’s inputs to this process are related to the emerging and preventive treatment of psychosocial troubles in the child and youth population, of the same way the project is associated to the community potentiation, the empowerment and the appropriation of children and young with the public space, all of this done through a model of intervention since the environmental and community psychology, complemented with the education of the people and the theater of the oppressed.